The impact of empowerment on employees’ performance at Bank Simpanan Nasional / Nuru Hafizah Khairudin - Khairudin, Nuru Hafizah (2013)
This research aims to investigate the relationship between empowerment and employee performance in the Malaysian banking industry. It also aims to examine the influence of empowerment on employee performance and to identify which of the three (3) dimensions of empowerment has the greatest influence over employees’ job performance. The three dimensions of empowerment namely competence, self determination and effect are the identified independent variables, with employees’ job performance as the dependent variable. Each of the dimensions of empowerment was tested to determine its relationship with employee performance. Questions on empowerment were adopted from Spreitzer (1995) 5-item questions on competence, self determination and effect. The questions on performance were adapted from Carly Webster’s (2006) empirical study on “An empirical analysis of the relationships between the interactive use of performance measurement systems, creativity and performance: the intervening role of psychological empowerment”. The questionnaires were distributed to employees who are currently working in the Headquarters of Bank Simpanan Nasional and 150 respondents were participated in the survey. Three (3) hypotheses were developed and tested using Descriptive Analysis, Pearson Correlation Coefficient and Regression Analysis. The findings indicate that employees in the banking industry find that empowerment strongly influences employees’ job performance. There is significant correlation between the dimensions of empowerment and employees’ job performance. They feel that when they are empowered with freedom and opportunities to influence decision making in their jobs or organisation, their performance will improve significantly. The implications of these findings are discussed and suggestions for future research are also identified and proposed.